Genome-wide open chromatin regions and their effects on the regulation of silk protein genes in Bombyx mori - Zhang, Quan (Sci Rep, 2017)
Nucleosome-depleted open chromatin regions (OCRs) often harbor transcription factor (TF) binding sites that are associated with active DNA regulatory elements. To investigate the regulation of silk-protein genes, DNA molecules isolated from the silk glands of third-day fifth-instar silkworm larvae and embryo-derived (BmE) cells were subjected to formal dehyde-assisted isolation of regulatory elements (FAIRE) and high-throughput sequencing. In total, 68,000 OCRs were identified, and a number of TF-binding motifs were predicted. In particular, OCRs located near silk-protein genes contained potential binding sites for functional TFs. Moreover, many TFs were found to bind to clusters of OCRs upstream of silk-protein genes, and to regulate the expression of these genes. The expression of silk protein genes may be related not only to regulating TFs (such as fkh, Bmdimm, and Bmsage), but also to developmental and hormone-induced TFs (such as zen, eve, Br, and eip74ef). Elucidation of genome-wide OCRs and their regulatory motifs in silk protein genes will provide valuable data and clues for characterizing the mechanisms of transcriptional control of silk protein genes.